ChemInform Abstract: A Metal‐Free Synthesis of Oxindoles by a Radical Addition‐Cyclization onto N‐Arylacrylamides with Xanthates. Issue 28 (25th June 2015) - Wang, Shucheng; Huang, Xuhu; Li, Bowen; Ge, Zemei; Wang, Xin; Li, Runtao
Abstract Various arylalkylation products including alkyl ester‐, benzyl‐, cyano‐, ketone‐, amine‐, and amide‐ substituted oxindoles are conveniently obtained.